Laboratorium Berita Digital: Pemberdayaan Siswa dalam Literasi Jurnalistik Menangkal Hoaks di Media Sosial - Rini Susiani; Ferlya Elyza; Syarifah Fadiya Hallaby; Alifya Zhavira; Reva Vahira Wita (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
This Community Service Program (PKM) aims to enhance news literacy and digital journalism skills among students at SMP Islam Cendikia Darussalam in response to the increasing spread of hoaxes on social media. The program was implemented through a participatory approach involving socialization, training, mentoring, and hands-on practice sessions with teachers and students. The training covered topics such as digital literacy, information verification techniques, accurate and balanced news writing, and the creation of creative anti-hoax content. The results indicated a significant improvement in students’ news literacy skills, with an average increase of 41.1%, and teachers’ digital journalism management skills, with an increase of 48.1%. Additionally, the program successfully established a digital news laboratory at the school to sustain media literacy initiatives. This activity positively impacted participants’ critical thinking, information ethics, and digital competencies, while fostering a productive and literacy-conscious school environment.